Clothing, memory and (de)identity construction (Revista de Ensino em Artes, Moda e Design, 2021)
The present study aims to analyze the existing connection between the clothing field and the memory field, identifying how the first mentioned area can act as a factor, both constructor and identity deconstructor. Initially, fundamental concepts are brought so that it is possible to discuss the subject, later, cases are presented that exemplify what was approached in a theoretical-conceptual way, such as pieces of clothing, currently preserved in museum institutions. The study is carried out by means of a bibliographic review and case study. Concluding that memory and identity are inseparable, and both can be modeled and remodeled just as clothing ismodeled on the body, it was understood that there is a direct link between the three concepts discussed here.
Keywords: Clothing; Memory; Identity